Mentoring Activities as an Effort to Increase Students Interest and Motivation in Learning - Arie Purwa Kusuma; Nurimani Nurimani; Deswita Deswita; Nurina Kurniasari Rahmawati; Rifa Atiyyah; Chrisnaji Banindra Yudha (Smart Society, 2022)
Pusat Kegiatan Belajar Masyarakat (PKBM) is a form of non-formal education institution owned and managed by the community. The purpose of this service is to provide a fun mathematics learning method for package students at PKBM, besides that this service also motivates students regarding the world of work and the world of campus that they will face after graduation.Â  The implementation method in this mentoring activity uses an approach and collaboration method. This service is carried out in PKBM N 17 Penjaringan for students who are currently taking education and their further education. Â After the activity was carried out, analysis and evaluation were carried out, and it was seen that the children experienced an increase in their understanding of mathematics, and students' motivation also increased in improving their future by continuing to college. This activity received a good response from PKBM students and is expected to continue to guide students in learning mathematics.